Flouting of Grice’s Maxims in Creating Humor in "Steve TV Show” YouTube Clips - Nafi', Mar' Atul Latifah Jauharin; Yuliasri, Issy; Pratama, Hendi (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study examines how the violation of Grice’s cooperative maxims—quantity, quality, relation, and manner—elicits humor in YouTube clips from Steve Harvey’s TV Show. Using a qualitative content analysis approach, this research analyzes social media data from the show’s YouTube channel. The analysis applies a pragmatic identity framework and follows the data analysis techniques outlined by Miles and Huberman (1984). Key findings reveal how different types of maxim violations, influenced by contextual factors, contribute to humor production in a talk show format. This study offers valuable insights into the role of conversational implicature in humor, particularly within contemporary media, and contributes to the broader field of discourse analysis and humor studies. By examining how humor is constructed through maxim flouting, the research highlights its implications for understanding humor in digital media and its cultural significance in global media contexts.